Pre-Migratory Movements by Juvenile Burrowing Owls in a Patchy Landscape - L. Danielle. Todd; Ray G. Poulin; R. Mark. Brigham; Erin M. Bayne; Troy I. Wellicome (Avian Conservation and Ecology, 2007)
Dispersal is a fundamental aspect of population dynamics, and can have direct implications on processes such as the colonization of habitat patches. Pre-migratory movements, landscape fragmentation, and body condition have all been hypothesized as key factors influencing dispersal in birds, but little direct evidence exists to support these ideas. We used radio-telemetry and supplementary feeding to test if body condition or landscape pattern influenced pre-migratory movements of juvenile Burrowing Owls (Athene cunicularia) in a fragmented landscape. We categorized grassland patches as either large (â¥95 ha) or small and isolated (â¤58 ha and â¥1.5 km to next nearest grassland patch), and young owls were either provided supplemental food as nestlings or not. Owlets receiving supplemental food and residing in large grassland patches moved a greater maximum distance from their nest than similarly fed owlets residing in small patches (large = 1605 ± 443 m; small = 373 ± 148 m). In contrast, non-supplemented owlets from large and small patches did not differ in their maximum distance moved from the nest (large = 745 ± 307 m; small 555 ± 286 m). Only two of 32 individuals from small patches moved >800 m, whereas ten of 23 owlets from large patches moved >800 m. In addition, owlets from large patches continued to move farther and farther from their nest before migration, whereas owlets in small, isolated patches ultimately moved